Rearrangement of the Endothelial Cell Cytoskeleton in Glomerular and Peritubular Capillaries (PTCS) Following Antibody-Mediated Rejection (AMR): Its Significance on the Development of Transplant Glomerulopathy and Interstitial Fibrosis. (July 2018) - Handan Ozdemir, B.; Nurhan Ozdemir Acar, F.; Ayva, Sebnem; Akcay, Eda; Ayvazoglu Soy, Ebru H.; Ozdemir, Gokce; Haberal, Mehmet
Abstract : Introduction: The actin cytoskeleton (CSK) is a critical regulator of various cellular functions in endothelial cells (ECs). The stability of CSK of ECs is necessary to sustain the EC barrier function, and its disruption can initiate EC permeability and therefore influx of leukocytes and proteinuria. The aim of this study was two-fold; first to understand whether AMR has an impact on the rearrangement of endothelial CSK both in glomeruli and PTCs and second to investigate the influence of CSK rearrangement on the development of transplant glomerulopathy (TG) and interstitial fibrosis (IF). Material and Methods: Total 116 patients included in the study. Biopsies of all cases with the diagnosis of AMR reevaluated and the intensity of interstitial, glomerular and PTC inflammation, neutrophil, macrophage and lymphocyte infiltration graded. HLA-DR expression of PTCs examined to determine the extension of the destruction of PTCs. The EC expression of CSK proteins F-actin, paxillin, vinculinand even HIF-1α, VEGF, and eNOSin glomeruli and PTCs evaluated. Follow-up biopsies analyzed for the development of TG and IF Results: Both the degree of the C4d expression and the degree of the PTC destruction found to increase with increasing amount of interstitial inflammation, glomerulitis, and PTC-itis (p<.001). Both in glomeruli and PTCs, the EC expression of F-actin paxillin, vinculin, HIF-1α, VEGF, and eNOS increased with increasing degree of C4d expression, PTC destruction, interstitial inflammation, glomerulitis and PTC-itis (p<.001). Also, the degree of the EC expression of F-actinpaxillin, vinculin, HIF-1α, VEGF, and eNOS increases with the increasing amount of macrophages and neutrophils in the PTCs and glomeruli (p<.001). Total 48 (41.4%) cases developed TG at a mean time of 17.8±7.2 months, 67 cases developed IF at a meantime of 22.5±11.3 months and 53 (45.7%) patients lost their graft at a mean time of 39±18 months. The inflammation of glomeruli, PTCs and interstitium showed significant positive correlation with the development of TG and IF (p<0.001). The risk of the development of TG, IF, proteinuria, and graft loss found higher in recipients with a high degree of F-actin, paxillin, vinculin, HIF-1α, VEGF and eNOS expression (p<.001). Conclusion: We hypothesized that PTC destruction following AMR causes chronic hypoxia that induces HIF-1α, VEGF and eNOS expression that give rise to the reorganization of EC cytoskeleton. Upon the reorganization of EC-CSK and the increased amount of endothelial VEGF together induce the formation of gaps between adjacent ECs, which in turn initiate EC permeability and therefore influx of leukocytes and proteinuria. As a consequence, the increasing amount of inflammatory cells induces the early development of IF, TG, and consequently the premature graft loss.